Impact of Part D low-income subsidies on medication patterns for Medicare beneficiaries with diabetes - Stuart, Bruce; Yin, Xianghua; Davidoff, Amy; Simoni-Wastila, Linda; Zuckerman, Ilene; Shoemaker, J Samantha; Doshi, Jalpa (Medical care, 2012)
It is not known whether low-income subsidies (LIS) under Medicare Part D help beneficiaries overcome impediments to medication use associated with poor socioeconomic status and high disease burden. To compare Medicare beneficiaries with LIS and Medicaid (duals), LIS without dual eligibility, and non-LIS recipients on use of medications recommended in diabetes treatment. Fixed-effect comparisons among beneficiaries in the same Part D plans in 2006-2007. Nationally representative sample of enrollees in Part D prescription drug plans. A total of 109,292 beneficiaries were in 204 prescription drug plans; 47.5% non-LIS, 44.4% duals, and 8.1% nondual LIS recipients. Medications included antidiabetic agents, renin-angiotensin-aldosterone system inhibitors, and antihyperlipidemics. Drug use was measured by exposure, duration of therapy, and medication possession ratio. The LIS dual cohort had significantly higher comorbidity compared with non-LIS comparisons, LIS nonduals were significantly more likely to take medications in all 3 drug classes compared with non-LIS recipients, but differences were small (between 2% and 4%; P<0.05). Non-LIS recipients and duals had equivalent exposure to any antidiabetic drug and antihyperlipidemics, but duals were 3% less likely to receive renin-angiotensin-aldosterone system inhibitors compared with non-LIS recipients (P<0.05). Small differences in adjusted values for duration of therapy and medication possession ratio among the 3 cohorts were also observed, none of which were clinically meaningful. Similarities in medication utilization among Part D enrollees with and without LIS coverage supports the program objective of providing enhanced access to needed medications for diverse groups of Medicare beneficiaries.